A molecular dynamics investigation of a free surface of liquid argon - Opitz, Azel Carl Louis (Department of Physics, 2016)
A molecular dynamics simulation technique is employed to investigate the equilibrium molecular structure of the liquid-vapour interfacial region for argon at about 124 °K. The density profile through the surface is found to be of a non-monotonic form. The pair distribution function in the surface is also determined and compared to radial distribution functions of the interior liquid. The surface tension and surface energy are also obtained and are found to be in agreement with generally accepted experimental values.